A reader in the anthropology of religion. - Lambek, Michael (Blackwell anthologies in social & cultural anthropology ;, 2008)
A Reader in the Anthropology of Religion is a collection of some of the most significant classic and contemporary writings in the field. Updated in its second edition, this volume examines numerous aspects of religion in a diversity of cultures and expands upon the idea of what we mean by ‘religion’, linking it to some of the broader questions of culture and politics -- Présentation de l'éditeur.